Effect of PbS impurity on crystallization mechanism of phosphate glasses studied by differential scanning calorimetry - Reynoso, VCS; Yukimitu, K.; Nagami, T.; Carvalho, C. L.; Moraes, João Carlos Silos [UNESP]; Araujo, E. B. (Elsevier B.V., 2002)
In this work, differential scanning calorimetry (DSC) was used to study effect of PbS impurity on crystallization mechanism of phosphate glasses. Bulk glasses presented one crystallization peak while powdered glasses presented two distinct crystallization peaks. For both undoped and doped glasses were determined the activation energies for the crystallization and the Avrami n parameters. The activation energies for undoped phosphate glass were 336 +/- 6 and 213 +/- 3 kJ mol(-1), respectively, associated with first and second crystallization peaks. For doped glass, the obtained energies were 373 +/- 9 and 286 +/- 7 kJ mol(-1). The calculated Avrami parameters, based on first crystallization peaks, for undoped and doped glasses were 2.25 +/- 0.01 and 1.75 +/- 0.02, respectively. These values suggest that the first DSC peak, in both glasses, may be associated with surface crystallization. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: phosphate glasses; crystallization; activation energy; Avrami parameter